Re-presenting the good society - Cooke, Maeve (Studies in contemporary German social thought., 2006)
A proposal for negotiating the tension between an anti-authoritarian impulse and a guiding idea of context-transcending validity in critical social theory. Contemporary critical social theories face the question of how to justify the ideas of the good society that guide their critical analyses. Traditionally, these more or less determinate ideas of the good society were held to be independent of their specific sociocultural context and historical epoch. Today, such a concept of context-transcending validity is not easy to defend; the "linguistic turn" of Western philosophy signals the widespread acceptance of the view that ideas of knowledge and validity are always mediated linguistically and that language is conditioned by history and context. In Re-Presenting the Good Society, Maeve Cooke addresses the justificatory dilemma facing critical social theories: how to maintain an idea of context-transcending validity without violating anti-authoritarian impulses. In doing so she not only clarifies the issues and positions taken by other theorists--including Richard Rorty, Jurgen Habermas, Axel Honneth, and Judith Butler--but also offers her own original and thought-provoking analysis of context-transcending validity. Because the tension between an anti-authoritarian impulse and a guiding idea of context-transcending validity is today an integral part of critical social theory, Cooke argues that it should be negotiated rather than eliminated. Her proposal for a concept of context-transcending validity has as its central claim that we should conceive of the good society as re-presented in particular constitutively inadequate representations of it. These re-presentations are, Cooke argues provocatively, regulative ideas that have an imaginary, fictive character